2015
DOI: 10.1136/bjophthalmol-2015-307161
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of trabeculectomy versus Ex-PRESS: 3-year follow-up

Abstract: NCT01263561; post results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 13 publications
(38 reference statements)
4
44
3
Order By: Relevance
“…In previous analyses using Ex-PRESS, it has been reported that the postoperative IOP after 2 years ranges from 12.1 to 14.7 mmHg. 8 , 11 13 Our results were thus slightly lower than those reported previously. This was at least partly due to the greater number of postoperative medications in our patients.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In previous analyses using Ex-PRESS, it has been reported that the postoperative IOP after 2 years ranges from 12.1 to 14.7 mmHg. 8 , 11 13 Our results were thus slightly lower than those reported previously. This was at least partly due to the greater number of postoperative medications in our patients.…”
Section: Discussioncontrasting
confidence: 95%
“…Many studies have compared conventional trabeculectomy and trabeculectomy with Ex-PRESS. 8 11 Ex-PRESS exhibits similar outcomes with fewer early postoperative complications because of its low rate of over-filtration. Other advantages of Ex-PRESS are that the lumen of the device is standardized constantly, and the outflow is predictable.…”
Section: Introductionmentioning
confidence: 96%
“…Success rates after trabeculectomy with target pressure between 18 and 22 mmHg have been variously reported to range from 43% to 86% without medications [1726] and from 59% to 98% with medications [17, 21, 22]. In our study, postoperatively, a complete success was possible in 64.7% with an IOP at final follow-up of <18 mmHg without medication and 82.35% with IOP <18 mmHg with two or less medications.…”
Section: Resultssupporting
confidence: 51%
“…EXP was developed in an effort to make filtration surgery more straightforward. Nonetheless, it seems that the efficacy and safety profile of the EXP are not superior to standard trabeculectomy [44][45][46][47]. Only a few studies directly comparing AGV and EXP have been published.…”
Section: Ahmed Glaucoma Valve Versus Ex-press Shuntsmentioning
confidence: 99%